2015
DOI: 10.1371/journal.pone.0130304
|View full text |Cite
|
Sign up to set email alerts
|

Does Dysphoria Lead to Divergent Mental Fatigue Effects on a Cognitive Task?

Abstract: ObjectiveTiredness, low energy, and listlessness are common symptoms to be associated with depression. The question remains to what extent these symptoms influence the effects of fatigue on sustained performance tasks, such as impaired task engagement and performance. Based on earlier findings, it was hypothesized that dysphoric (i.e., mildly depressed) individuals, compared to healthy controls, would display earlier fatigue onset and more severe fatigue effects on task engagement and performance during a cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Nine of the studies conducted multi-modal measurement of fatigue using EEG (Gergelyfi et al, 2015;Guo et al, 2018;Hopstaken et al, ,2015Hopstaken et al, , , 2015aHopstaken et al, , , 2016Sengupta et al, 2017;Wang et al, 2019), ECG (Abbasi et al, 2018;Horiuchi et al, 2018), and functional near-infrared spectroscopy (fNIRS; Borragán et al, 2018) and were able to confirm the corresponding measurements of mental fatigue using eyebased metrics.…”
Section: Mental Fatigue Recording Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nine of the studies conducted multi-modal measurement of fatigue using EEG (Gergelyfi et al, 2015;Guo et al, 2018;Hopstaken et al, ,2015Hopstaken et al, , , 2015aHopstaken et al, , , 2016Sengupta et al, 2017;Wang et al, 2019), ECG (Abbasi et al, 2018;Horiuchi et al, 2018), and functional near-infrared spectroscopy (fNIRS; Borragán et al, 2018) and were able to confirm the corresponding measurements of mental fatigue using eyebased metrics.…”
Section: Mental Fatigue Recording Methodsmentioning
confidence: 99%
“…In contrast, Song et al (2015) found a negative correlation between the mean blink duration and the fatigue score, although the fatigue score increased with time on a spacecraft-support control task that lasted for 1 hr 45 min. Another inexplicable result is the lack of a pattern for the baseline pupil diameter in one study (Hopstaken et al, 2015b), although the same cognitive task performed for a similar amount of time (~2 hr) in similar experimental conditions resulted in a decrease in the baseline pupil diameter (Hopstaken et al, 2015a(Hopstaken et al, , 2015.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the end of every trial, the participants answered the effort question from NASA—Task Load Index questionnaire (NASA-TLX) on a seven-point Likert scale, by selecting a number using eye-tracking on the on-screen keyboard, in response to the question on the screen, thereby reporting the perceived effort during the trial. Before starting the experiment each day and after every session, a question on the subjective level of fatigue on a seven-point Likert scale was orally answered by the participants [ 16 ]. The experiment design is shown in Fig 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The effort question from NASA-TLX was selected to focus on the perception of the effort applied by the participants on the tasks. A single-item measure using the word tired was used to define the fatigue level [ 16 , 44 ]. The experiment required cognitive processing, and did not involve any physical activity.…”
Section: Methodsmentioning
confidence: 99%